The relationship of hip fracture and thyroid disorders: a systematic review - SeyedAlinaghi, SeyedAhmad; Yarmohammadi, Soudabeh; Dashti, Mohsen; Ghasemzadeh, Afsaneh; Siami, Haleh; Molla, Ayoob; Mahrokhi, Sona; Qaderi, Kowsar; Arjmand, Ghazal; Parikhani, Sahar Nooralioghli; Amrollah, Masoomeh Fathi; Mirghaderi, Peyman; et al. (Frontiers in Endocrinology, 2023)
Introduction: Bone density regulation is considered one of the systems affected by thyroid hormones, leading to low bone density that can result in pathologic fractures, including hip fractures. This review aimed to update clinicians and researchers about the current data regarding the relationship between hip fractures and thyroid disorders. Methods: English papers were thoroughly searched in four main online databases of Scopus, Web of Science, PubMed, and Embase. Data extraction was done following two steps of screening/selection using distinct inclusion/exclusion criteria. This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist and the Newcastle-Ottawa Scale (NOS) as bias assessment. Results: In total, 19 articles were included in the research. The risk of hip fractures in women with differentiated thyroid cancer (DTC) is higher than hip fractures caused by osteoporosis. Men with hyperthyroidism and subclinical hyperthyroidism are at higher risk for hip fracture. Also, a decrease in serum thyroid stimulating hormone (TSH) may be associated with an increased risk of hip fracture. Conclusion: Reaching a consensus conclusion regarding the association between subclinical thyroid dysfunction and hip fracture is not feasible due to the heterogenicity of evidence; however, there may be a higher risk of fracture in individuals with subclinical hyperthyroidism.